Synthesis of 7,3'-Epoxy-8,4'-Oxyneolignane-1’-Carboxylic Acid from Natural Eusiderin A and its Activity Against Trichophyton mentagrophytes - Muhaimin, Muhaimin; Syamsurizal, Syamsurizal; Latief, Madyawati; Iskandar, Rahmi; Chaerunisaa, Anis Y.; Mujahidin, Didin (Current Organocatalysis, 2020)
Background: Eusiderin A is a neolignan derivate, which makes up the majority of the secondary metabolite of Eusideroxylon zwageri. It has been reported as a potent biopesticide and antifungal agent. Previous studies on the oxidation of terminal methylene of the allylic chain in Eusiderin A have been able to produce primary alcohol, pinacol, and an aldehyde which demonstrated strong activity against plant pathogenic fungi, therefore activity against dermal fungi needs to be studied. Objective: The current study aims to improve the hydrophilicity of Eusiderin A via oxidation of the allylic chain in order to derive a potent antifungal property. Methods: Transformation of Eusiderin A has been achieved by using the Wacker Oxidation Method in combination with the α-Hydroxylation-Ketone Method to produce 7,3’-epoxy-8,4’-oxyneolignane-1’- carboxylic acid. The structure of the 7,3’-epoxy-8,4’-oxyneolignane-1’-carboxylic acid was identified from spectroscopy data. The in vitro antifungal activity study was performed using the paper disc diffusion method against Trichophyton mentagrophytes. Results: New molecule of natural Eusiderin A through the oxidation of the allylic chain to increase the hydrophilicity of Eusiderin A has been designed. Based on the observed UV, IR, 1H and 13C-NMR, and MS spectra, it can be stated that the 7,3’-epoxy-8,4’-oxyneolignane-1’-carboxylic acid has been formed. At a concentration of 50 ppm, this compound showed antifungal activity against Trichophyton mentagrophytes. Conclusion: It can be concluded that the 7,3’-epoxy-8,4’-oxyneolignane-1’-carboxylic acid is a potent antifungal agent as it is able to inhibit the Trichophyton mentagrophytes colonies growth.
Keywords: oxidation